2009
DOI: 10.1143/jpsj.78.113701
|View full text |Cite
|
Sign up to set email alerts
|

Upper Critical Fields of the 11-System Iron-Chalcogenide Superconductor FeSe0.25Te0.75

Abstract: We have performed electrical resistivity measurements of a polycrystalline sample of FeSe 0.25 Te 0.75 , which exhibits superconductivity at T c ∼ 14 K, in magnetic fields up to 55 T to determine the upper critical field µ 0 H c2 . In this compound, very large slopes of µ 0 H c2 at the onset, the mid-point, the zero-resistivity temperatures on superconductivity are determined to be −13.7, −10.1, and −6.9 T/K, respectively. The observed µ 0 H c2 (T )s of this compound are considerably smaller than those expecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 21 publications
12
69
0
Order By: Relevance
“…Moreover, It has been reported that the zero temperature upper critical field of disordered superconductor shows deviation from the conventional one band WHH model and the observed values of H C2 (0) are smaller than the estimated values from conventional WHH model. [31][32][33][34][35][36][37][38] Similar deviation is also expected in our measurements. The broadening of the superconducting transition width in applied magnetic field is strongly related to the thermally activated flux flow mechanism.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, It has been reported that the zero temperature upper critical field of disordered superconductor shows deviation from the conventional one band WHH model and the observed values of H C2 (0) are smaller than the estimated values from conventional WHH model. [31][32][33][34][35][36][37][38] Similar deviation is also expected in our measurements. The broadening of the superconducting transition width in applied magnetic field is strongly related to the thermally activated flux flow mechanism.…”
Section: Resultssupporting
confidence: 90%
“…It indicates that the spin-paramagnetic effect is the dominant pair-breaking mechanism for both H ab and H c [110,111,114]. For the Fe(Te,Se) in the clean limit (grown by Bridgman-Stockbarger technique) the µ 0 H c2 (T ) is Pauli limited.…”
Section: Features Of µ 0 H C2 (T ) In Iron Chalcogenide Superconductorsmentioning
confidence: 99%
“…The T c of FeSe is increased up to 15 K by partial substitution of Te or S for Se and it is also increased up to ϳ27 K by applying hydrostatic pressure of 1.48 GPa. 3,[11][12][13][14][15] The effect of pressure on superconductivity, i.e., dT c / dP is around 9.1 K/GPa, which is four times more than for any other known superconductor until date. Very high dT c / dP of FeSe warrants large scope for increasing its T c by chemical pressure through on site substitutions.…”
Section: Introductionmentioning
confidence: 99%